Bedaquiline and Delamanid Combination Treatment of 5 Patients with Pulmonary Extensively Drug-Resistant Tuberculosis - Maryandyshev, Andrey; Pontali, Emanuele; Tiberi, Simon; Akkerman, Onno; Ganatra, Shashank; Sadutshang, Tsetan Dorji; Alffenaar, Jan-Willem; Amale, Rohit; Mullerpattan, Jai; Topgyal, Sonam; Udwadia, Zarir Farokh; Centis, Rosella; et al. (Emerging infectious diseases, 2017)
We report the experiences of 5 patients taking bedaquiline with delamanid in combination: 1 patient was cured; 3 culture converted, with 2 continuing and 1 changing therapy; and 1 died from respiratory insufficiency. For 2 patients, QT-interval prolongation but no arrhythmias occurred. Use of this therapy is justified for patients with limited options.